UNDERSTANDING THE IMPACT OF MENINGEAL WORM, PARELAPHOSTRONGYLUS TENUIS, ON MOOSE POPULATIONS - Lankester, Murray Wayne (Lakehead University, 2010)
Periodic declines in moose (Alces alces) populations have occurred repeatedly during the past century on the southern fringe of moose range in central and eastern North America. These slow declines, occurring over a number of years, are associated with higher than usual numbers of co-habiting white-tailed deer (Odocoileus virginianus). Numerous proximate causes have been hypothesized but none has gained widespread acceptance among cervid managers. However, current knowledge of the nature of moose declines and the biology of meningeal worm (Parelaphostrongylus tenuis) makes this parasite the most credible explanation. Other suggested disease-related causes are rejected, including infection with liver flukes (Fascioloides magna) because there is no clinical evidence that flukes kill moose. As well, this parasite occurs at only moderate prevalence and intensity in some jurisdictions and is completely absent in others where moose declines are known. Winter ticks (Dermacentor albipictus), on the other hand, do kill moose but usually have a distinctly different and more immediate impact on populations. It is recognized that moose, albeit at lower density, can persist for extended periods in the presence of P. tenuis-infected deer at moderate densities. However, it is argued here that parelaphostrongylosis can, when conditions favour sustained high deer densities and enhanced gastropod transmission, cause moose numbers to decline to low numbers or to become locally extinct. Short, mild winters favour deer population growth in areas previously best suited for moose. Wetter and longer snow-free periods increase the numbers and availability of terrestrial gastropod intermediate hosts and the period for parasite transmission. It is hypothesized that these climatic conditions increase rates of meningeal worm transmission to moose and of disease, primarily among younger cohorts. Reports of overtly sick moose are common during declines but may not account for the total mortality and morbidity caused by meningeal worm. ...